2012 IEEE/ASME International Conference on Advanced Intelligent Mechatronics (AIM) 2012
DOI: 10.1109/aim.2012.6266022
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of surface-normal measurement in robotic drilling for aircraft fuselage using three laser range sensors

Abstract: Surface-normal measurement is an essential part in robotic drilling system. A novel method to measure the surface-normal of aircraft skin is proposed in this paper. Resumptively, three laser range sensors evenly distributed around the drill bit are used to measure the distance from them to aircraft skin within a small area. So the coordinates of three measured points can be obtained, and the normal vector is calculated from the cross product of any two vectors that are tangent to the surface at the drilling po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…When x = l 0 , y = m 0 , t = 1 , we can get the conical surface Eq. (15). in which Assuming l 0 = 0, m 0 = 0, n 0 = −k in point O ′ , we can get the simplified Eq.…”
Section: Solving Turning Angle β Through Camera Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…When x = l 0 , y = m 0 , t = 1 , we can get the conical surface Eq. (15). in which Assuming l 0 = 0, m 0 = 0, n 0 = −k in point O ′ , we can get the simplified Eq.…”
Section: Solving Turning Angle β Through Camera Visionmentioning
confidence: 99%
“…There are three standard methods to measure the normal direction of the reference hole, which are eddy current, mechanical contact, and laser non-contact. Among them, non-contact laser measurements are the most widely used [13][14][15]. Multiple LDSs can be used in various layouts in the actual measurement, such as rectangular uniform layouts [4] and triangular layouts [16].…”
Section: Introductionmentioning
confidence: 99%
“…Calderon [7] put forward an algorithm for surface normal determination using a neighborhood strategy based on local piecewise planes, and this algorithm greatly improved the accuracy of surface normal determination. Gong [8] proposed a novel method to measure the surface normal of an aircraft skin in order to improve the precision and efficiency of hole drilling. For aircraft panel mirror milling, Zhang [9] found that surface normal was critical to ensuring that the cutting tool path be consistent with the skin surface being machined.…”
Section: Introductionmentioning
confidence: 99%
“…Laser displacement sensors are commonly used non-contact measurement sensors, which have many advantages such as high-precision, low power consumption, high reliability and security [ 10 ]. Typically, three or four laser displacement sensors are installed on the pressure foot for surface normal measurement [ 11 , 12 ]. Due to the machining error of the pressure foot and the assembly errors, there are always small errors between the nominal and actual zero points and laser beam directions of laser displacement sensors.…”
Section: Introductionmentioning
confidence: 99%